2017
DOI: 10.7307/ptt.v29i3.2265
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Calming Measures: An Evaluation of the Effect on Driving Speed

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Positive effects for a similar broader set of indicators are also reported in a study from the United Kingdom [57], which monitored and evaluated nine pilot areas for the conversion of residential neighbourhoods into calm residential zones (so-called Home zones), and in a report from Vitoria-Gasteiz in Spain [58], which examined the setup of a pilot traffic-friendly area (so-called Superblock). These two documents are a rare example of monitoring and evaluating a wider range of comprehensive traffic calming effects as opposed to a large number of studies focusing on traffic safety and vehicle flows and speeds reduction [23,[59][60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects for a similar broader set of indicators are also reported in a study from the United Kingdom [57], which monitored and evaluated nine pilot areas for the conversion of residential neighbourhoods into calm residential zones (so-called Home zones), and in a report from Vitoria-Gasteiz in Spain [58], which examined the setup of a pilot traffic-friendly area (so-called Superblock). These two documents are a rare example of monitoring and evaluating a wider range of comprehensive traffic calming effects as opposed to a large number of studies focusing on traffic safety and vehicle flows and speeds reduction [23,[59][60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…If obtained values are compared with previous studies in the literature, it must be said that Ewing [29] indicated a speed increase between 0.26 and 0.53 km/h every additional 10 m distance and in this study speed increases between 0.55 and 0.75 km/h were obtained, implying that at present, drivers tend to accelerate more rapidly between TCMs. Vaitkus et al [57] recommended a maximum distance of 200 m, 100 m, and 75 m, for speed limits of 50 km/h, 40 km/h and 30 km/h, respectively. Using developed models, for a V 85 of 50 km/h a maximum distance of 200 m is also recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Kveladze and Agerholm [55] observed that variable spacing influenced the median speed in the intermediate points of the segments, but without providing any specific relationship. Yeo et al [56] analyzed the influence of speed humps on the 85th percentile of the speed distribution and suggested that a spacing of 20 m to achieve a speed of 30 km/h, and a maximum of 70 m. Similarly, Vaitkus et al [57] concluded that when two TCMs were spaced more than 200 m, drivers accelerate until 10 km/h over the speed limit of 50 km/h and recommended a spacing of 150-200 m, 100 m and 75 m for speed limits of 50, 40 and 30 km/h, respectively. Therefore, the aim of this paper is to analyze the speed in the intermediate points between vertical traffic calming measures and relate it with the distance between them to propose models for predicting the speed in those midpoints.…”
mentioning
confidence: 99%
“…The experience of EU cities that have completed the process of developing and implementing SUMPs indicates that this results in economic benefits [65,66], benefits from reducing dependence on cars [67], benefits from traffic calming measures [68,69], and benefits for cyclists' safety [70] and traffic safety as a whole [71], thus achieving the final goal of improving quality of life for all citizens [16,72]. Based on these experiences, it is realistic to expect that the implementation of the SUMP will provide a better quality of life for the citizens of Podgorica.…”
mentioning
confidence: 99%